Mapping quantitative trait loci in chickpea associated with time to flowering and resistance to Didymella rabiei the causal agent of Ascochyta blight - Lichtenzveig, Judith; Bonfil, D.; Zhang, H.; Shtienberg, D.; Abbo, S. (Springer, 2006)
Drought is the major constraint to chickpea (Cicer arietinum L.) productivity worldwide. Utilizing early-flowering genotypes and advancing soring from spring to autumn have been suggested as strategies for drought avoidance. However, Ascochyta blight (casual agent: Didymella rabiei (Kov.) v. Arx.) is a major limitation for chickpea winter cultivation. Most efforts to introgress resistance to the pathogen into Kabuli germplasm resulted in relatively late flowering germplasm. With the aim to explore the feasibility of combining earliness and resistance, RILs derived from a cross between a Kabuli cultivar and a Desi accession were evaluated under field conditions and genotyped with SSR markers. Three quantitative trait loci (QTLs) with significant effects on resistance were identified: two linked loci located on LG4 in epistatic interaction and a third locus on LG8. Two QTLs were detected for time to flowering: one in LG1 and another on LG2. When resistance and time to flowering were analyzed together, the significance of the resistance estimates obtained for the LG8 locus increased and the locus effect on days to flowering, previously undetected, was significantly different from zero. The identification of a locus linked both to resistance and time to flowering may account for the correlation observed between these traits in this and other breeding attempts.